Effects of Phytosterols supplementation on blood glucose, glycosylated hemoglobin (HbA1c) and insulin levels in humans: a systematic review and meta-analysis of randomized controlled trials - Salehi-Sahlabadi, Ammar (J Diabetes Metab Disord, 2020)
BACKGROUND: In the literature, there are still controversies regarding the effect of phytosterol(PS) supplementation on fasting blood sugar (FBS), insulin levels and glycosylated hemoglobin (HbA1c) in humans. We aimed to assess the impact of PS supplementation on FBS, HbA1c and insulin levels by conducting a systematic review and meta-analysis of the available randomized controlled trials (RCTs). METHODS: A comprehensive search was conducted to identify all RCTs published up to May 2019 in the following databases: PubMed-MEDLINE, Web of Science, Cochrane Library and Scopus. The mean difference with 95% confidence intervals (CIs) was pooled using a random-effects model (DerSimonian-Laird method). RESULTS: Twenty-six arms from 20 RCTs were included in the present meta-analysis. Our findings show that PS supplementation decreases insulin levels (mean difference [MD]: −6.426 μU/ml, 95% CI: −7.187, −5.665, P- value = 0.000). However, PS supplementation did not have significant effects on FBS and HbA1c levels. Following PS supplementation, significant changes in FBS (mean difference [MD]: −1.942 mg/dl, 95% CI: −3.637, −0.246, P- value = 0.025) and HbA1c (mean difference [MD]: −0.059%, 95% CI: −0.114, −0.004, P- value = 0.035) based on PS dosage (mg/d) were recorded. CONCLUSIONS: In patients with a baseline BMI <25 kg/m(2), PS consumption significantly increased FBS levels. Patients who consumed 1–2 g/day of PS had a lower FBS and lower HbA1c levels. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40200-020-00526-z) contains supplementary material, which is available to authorized users.